Lacticaseibacillus rhamnosus Hao9 exerts antidiabetic effects by regulating gut microbiome, glucagon metabolism, and insulin levels in type 2 diabetic mice - Han, Mei; Liao, Wenyan; Dong, Yao; Bai, Chen; Gai, Zhonghui (Frontiers in Nutrition, 2023)
Introduction Type 2 diabetes mellitus (T2DM) is a metabolic disease that has led to a significant global public health burden. Methods In this work, we investigated the effects of Lacticaseibacillus rhamnosus Hao9 on T2DM in mice with high-fat diet- and streptozotocin (STZ)-induced diabetes (diabetic mice) and explored the underlying mechanisms. Results We found that 109 colony forming units (CFUs) of Hao9 per day significantly reduced fasting blood glucose and insulin levels (p < 0.001) in diabetic mice. Moreover, Hao9 enhanced liver antioxidant capacity and significantly decreased glucose-6-phosphatase and phosphoenolpyruvate carboxykinase expression in the livers of diabetic mice (p < 0.001). Hao9 also reduced the serum concentrations of pro-inflammatory cytokines such as tumor necrosis factor alpha (TNFα), interleukin-1β (IL1β), and IL6 (p < 0.05) and improved intestinal barrier function in diabetic mice. The composition of the gut microbiome was modulated by Hao9, with an increased abundance of Roseburia, Eubacterium, and Lacticaseibacillus, and decreased abundance of Escherichia/Shigella. Notably, Lacticaseibacillus was detected at both weeks 5 and 12 post-treatment, suggesting sustained colonization of the gut by Hao9. Discussion The supplementation of Hao9 improved gut microbiota, glucose metabolism, and insulin levels significantly in T2DM mice. That means Hao9 contributes to improving T2DM symptoms with its potential beneficial effects. Therefore, Hao9 is a promising dietary supplement for the treatment of T2DM.